"Profile Of Patients with Allergic Rhinitis: A Total Nasal Symptom Score and Epworth Sleepiness Scale Based Study at RSUD Dr. Soetomo Hospital, Surabaya, Indonesia" - Charista Rusli, Alvina; Pawarti, Dwi Reno (Journal of Neonatal Surgery, 2025)
Profile of Patients with Allergic Rhinitis: A Total Nasal Symptom Score and Epworth Sleepiness Scale Based Study at RSUD Dr. Soetomo Hospital, Surabaya, Indonesia Allergic rhinitis (AR) is a chronic inflammatory disease mediated by immunoglobulin (Ig) E in the nasal mucosa and stimulated by allergen exposure. This retrospective study evaluated the demographic and clinical profiles of allergic rhinitis (AR) patients in an adult outpatient clinic utilizing the Total Nasal Symptom Score (TNSS) and Epworth Sleepiness Scale (ESS), which assess nasal symptoms and sleep quality, respectively. Data were collected from the Allergy-Immunology Division of the Otolaryngology outpatient clinic at RSUD Dr. Soetomo Hospital in Surabaya, from January 2019 to December 2021, including TNSS scores, ESS scores, age, gender, occupation, and education level. Among 188 patients, 116 (61.7%) met the inclusion and exclusion criteria. Of these, 71 (61.21%) were female and 45 (38.79%) males. Ages ranged from 18 to 64 years with a mean of 32.44 years. The 20-29 age group was most affected by AR (50%). The majority of subjects had a normal BMI (40.52%), were self-employed (31.03%), and had university-level education (48.28%). Combined symptoms were present in 99.14% of subjects, significantly more than those with a single symptom. Mild nasal symptoms were prevalent (44.83%), with sneezing being the most frequent. A normal ESS was observed in 63.79%, with "sitting quietly after lunch without alcohol" being the primary cause of daytime somnolence in 109 (93.97%) subjects. Sleepiness was least reported when "riding in a car as a passenger for 1 hour without rest" (53.45%). This study demonstrated that, although the largest ESS group was within the normal range, the majority of patients exhibited symptoms of excessive daytime somnolence, while the TNSS was predominantly mild. These findings suggest potential avenues for further research to analyze the effects of AR on sleep quality.